The Efficacy of Green Organic Fertilizer on the Growth and Health of Mango Tree (Mangifera Indica) - Supian N. Suhaibah; Kadir A.A.; Zin N.S.M.; Hissham N.F.N.; Supian N.S.; Detho A. (E3S Web of Conferences, 2023)
In Malaysia, 98% of garden waste is being dumped in the landfills. Meanwhile, only 2% is being recycled or compost. This is because no specified policy or guidelines focusing on garden waste management, and it often collected separately due to its bulk/large in size caused higher disposal cost. In this study, composting of organic fertilizer (OF) was performed to determine the effectiveness using two types of decomposition medium [leaf mold (LM) and green grass] and to evaluate the growth and health status of the Mango Tree (Mangifera Indica). Six different types of soil samples were collected at two-weeks intervals over a three-months period during the composting process. The 6 of tree plots physical monitoring analysis consists of height and diameter of tree and physicochemical parameters tested included pH, total nitrogen (TN), total phosphorus (TP), potassium (K), and heavy metals was performed. Results showed growth and health for plotted tree sample using dripping of OF is more higher and healthy than others. While, N, P and K analysis contents were obviously responsive to the treatments and followed the same trend in wide areas. The result showed highest levels treated with (LM+OF) by dripping automatic system. While, both plot of (LM+OF) manual and both plot (LM) treatments showed significantly the same effectiveness and came second statistically in this regard. In contrast, the lowest values were generally found in plot (control). It was concluded that OF has better effects on plant growth and soil quality with the N, P, and K concentration content. Our results indicate that the residues from the fermentation of organic fertilizers can be widely used.